Pseudo Alopecia Areata Caused by Skull-caps with Metal Pin Fasteners used by Orthodox Jews in Israel - Chaim Yosefy; Meir Ronnen; Dennis Edelstein (Clinical and Developmental Immunology)
Background: Alopecia Areata (AA) is a disease characterized by hair loss that is widely believed to be autoimmune in origin. Thus treatment is generally aimed in this direction using immune inhibitors such as steroids and PUVA.